The BAG: basic assessment guide for human well-being - Colfer, C.J.P. (Center for International Forestry Research, 1999)
The Basic Assessment Guide for Human Well-Being (or The BAG) focuses on the social criteria and indicators for sustainable forest management, a topic that has been the subject of considerable controversy and uncertainty. It is designed for people interested in assessing sustainable forest management, but who do not have a high degree of expertise in social sciences. The six simple methods described in this manual are designed for use by biophysical scientists with a college education. They can also be used by assessors with higher levels of expertise in social sciences, but they are presented in a ‘cookbook’ format. The Scoring and Analysis Guide, meant to be used with The BAG, provides additional help in making assessments of human well being, including a specific scoring method. It also provides increasingly detailed levels of guidance in analysis.